Presumed consent for transplantation: a dead issue after Alder Hey?. Issue 3 (1st June 2003) - English, V; Sommerville, A
Abstract : In the wake of scandals about the unauthorised retention of organs following postmortem examination, the issue of valid consent (or the lack of it) has returned to the forefront. Emphasis is put on obtaining explicit authorisation from the patient or family prior to any medical intervention, including those involving the dead. Although the controversies in the UK arose from the retention of human material for education or research rather than therapy, concern has been expressed that public mistrust could also adversely affect organ donation for transplantation. At the same time, however, the British Medical Association (BMA) continues to call for a shift to a system of presumed consent for organ transplantation. This apparent inconsistency can be justified because valid distinctions exist between the reasons requiring explicit consent for retention and the acceptability of presumed consent for transplantation. This paper argues for introducing a system of presumed consent for organ donation, given the overwhelming expressions of public support for transplantation. Ongoing legislative review in the UK provides an ideal chance to alter the default position to one where potential donors can simply acquiesce or opt out of donation. Combined with consultation with their relatives, this could be a much better method of realising individuals' wishes. It would also achieve a better balance between the duties owed to the deceased and those owed to people awaiting a transplant.